Angiotensin-related genetic determinants of cardiovascular disease in patients undergoing hemodialysis. Issue 11 (2nd July 2018) - Moe, Sharon M; Long, Jin; Schwantes-An, Tae-Hwi Linus; Decker, Brian S; Wetherill, Leah; Edenberg, Howard J; Xuei, Xiaoling; Vatta, Matteo; Foroud, Tatiana M; Chertow, Glenn M
Abstract: Background: Cardiovascular mortality in patients receiving dialysis remains unacceptably high, with unexplained ancestry differences suggesting a genetic component. Methods: We analyzed DNA samples from 37% of subjects enrolled in the EValuation Of Cinacalcet Hydrochloride (HCl) Therapy to Lower CardioVascular Events (EVOLVE) trial, a randomized trial conducted in patients receiving hemodialysis with secondary hyperparathyroidism, comparing cinacalcet to placebo on a background of usual care. DNA was analyzed for single-nucleotide polymorphisms (SNPs) in the genes encoding the angiotensin-converting enzyme receptor type I ( AGTR1 ) and angiotensin-converting enzyme ( ACE ). Survival analyses were conducted separately in European Ancestry (EA) and African Ancestry (AfAn) due to known differences in cardiovascular events, minor alleles for the same variant and the frequency of minor alleles. Our primary determination was a meta-analysis across both races. Results: Meta-analysis showed significant associations between rs5186 in AGTR1 and increased rates by 25–34% for the primary endpoint (composite of death or nonfatal myocardial infarction, hospitalization for unstable angina, heart failure or peripheral vascular event), all-cause mortality, cardiovascular mortality and heart failure; all P < 0.001. Three correlated SNPs in ACE were associated with lower rates of sudden cardiac death (SCD) in EA samples. One ACE SNP, rs4318, only found in the AfAn samples, was associated with a lower rate of SCD in the AfAn samples. Conclusions: The C allele in rs5186 in AGTR1 was associated with higher rates of death and major cardiovascular events in a meta-analysis of EA and AfAn patients with end-stage kidney disease. SNPs in ACE were associated with SCD.